Analisis Pemanfatan Alam sekitar dalam Pembelajaran IPA di SDN Pakusari 2 - Shafa salsabyla anggitania; Muhammad Suwignyo Prayogo; Nadia haibatun nissa (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2025)
This study seeks to explore how the surrounding environment is utilized as a learning resource in science education at elementary schools and madrasah ibtidaiyah (SD/MI). A descriptive qualitative approach is applied, with data gathered through methods such as observation, interviews, and documentation. The data analysis process involves stages of data reduction, data display, and conclusion drawing. The findings show that utilizing the surrounding environment enhances students' understanding of science concepts, improves learning motivation, and encourages scientific inquiry. Teachers use various natural objects such as plants, water sources, and weather phenomena as learning media. However, the research also identifies several challenges, including limited time allocation and lack of teacher creativity in optimizing environmental resources. Overall, the study concludes that integrating local environmental elements into science learning makes learning experiences more contextual, meaningful, and effective for elementary students.